Polyfuran-based chemical sensors: Identification of promising derivatives via DFT calculations and fully atomistic reactive molecular dynamics - Lascane, Leonardo G. [UNESP]; Oliveira, Eliezer F.; Galvão, Douglas S.; Batagin-Neto, Augusto [UNESP] (Elsevier, 2020)
Organic polymers are promising materials for the design of active layers of chemical sensors. In this context, polyfuran (PF) derivatives have not been largely investigated, mainly due to stability problems and poorer electrical properties. Recent works have demonstrated that some of these typical drawbacks can be overcome by an appropriate choice of side groups, allowing the application of these compounds in varied areas, including in chemical sensors. To better evaluate the sensory features of these materials, electronic structure calculations (DFT) and fully atomistic reactive molecular dynamics (FARMD) simulations were conducted to investigate the local reactivity and analyze possible adsorption processes. The obtained results indicate the compounds PF-CCH and PF-NO2 as the most promising materials for the development of chemical sensors. These derivatives present high reactivity on the side groups, high stability to oxidation and good responses to the presence of analytes. Our results also indicate that the analysis of local reactivities via DFT (condensed-to-atoms Fukui indexes) and FARMD simulations can be used in a complementary way to evaluate polymer sensory properties and adsorption processes.
Keywords: Chemical sensors; Condensed-to-atoms Fukui indexes; Density functional theory; Molecular dynamics with reactive force fields; Polyfuran derivatives